2012
DOI: 10.1155/2012/161205
|View full text |Cite
|
Sign up to set email alerts
|

Antilithiasic and Hypolipidaemic Effects ofRaphanus sativusL.var. nigeron Mice Fed with a Lithogenic Diet

Abstract: In Mexico, Raphanus sativus L. var. niger (black radish) has uses for the treatment of gallstones and for decreasing lipids serum levels. We evaluate the effect of juice squeezed from black radish root in cholesterol gallstones and serum lipids of mice. The toxicity of juice was analyzed according to the OECD guidelines. We used female C57BL/6 mice fed with a lithogenic diet. We performed histopathological studies of gallbladder and liver, and measured concentrations of cholesterol, HDL cholesterol and triglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
3
2
0
Order By: Relevance
“…In vitro and in vivo studies carried out with a radish extract alone or mixed with other vegetables have observed an improvement of some obesity-related parameters, such as the accumulation of fat or the modulation of adipokines such as adiponectin. 106 , 110 Thus, the results obtained regarding the decrease in interleukin IL-6 are consistent with the literature.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In vitro and in vivo studies carried out with a radish extract alone or mixed with other vegetables have observed an improvement of some obesity-related parameters, such as the accumulation of fat or the modulation of adipokines such as adiponectin. 106 , 110 Thus, the results obtained regarding the decrease in interleukin IL-6 are consistent with the literature.…”
Section: Resultssupporting
confidence: 90%
“…The intracellular level of accumulated lipids was not modified with the treatment (Mbasal: 1.00 ± 0.11 vs Mtt: 1.02 ± 0.13); however, ADIPOQ showed a tendency toward reduced levels (Mbasal: 1.00 ± 0.15 vs Mtt: 0.77 ± 0.21), and IL-6 showed a significant reduction (Mbasal: 1.00 ± 0.28 vs Mtt: 0.031 ± 0.004) (Figure ). In vitro and in vivo studies carried out with a radish extract alone or mixed with other vegetables have observed an improvement of some obesity-related parameters, such as the accumulation of fat or the modulation of adipokines such as adiponectin. , Thus, the results obtained regarding the decrease in interleukin IL-6 are consistent with the literature.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Its pharmacological activities are antiurolithiasic, antimutagenic, antimicrobial, anticancer, antiproliferative hepatoprotective, and antioxidant. Castro-Torres et al 10 reported its efficacy in kidney stones.…”
Section: Discussionmentioning
confidence: 99%
“…Some people drink radish juice in pursuit of certain health benefits. One study showed that drinking radish juice lowered blood cholesterol and triglyceride levels in mice compared with the control group, which only drank water (Castro-Torres et al, 2012). However, little information is available regarding the effects of radishes themselves.…”
Section: Introductionmentioning
confidence: 99%